Major Depression In The Canadian Armed Forces: A Study of Incidence and Mental Health Service Use - Thériault, François (Université d'Ottawa / University of Ottawa, 2020)
Major depression is prevalent and impactful in military populations, and not all depressed military personnel access mental health services. However, the rate at which military personnel become depressed, and the likelihood that they will subsequently seek care, remains poorly understood. In this thesis, I present four distinct studies that have helped bridge existing knowledge gaps. First, I used data from a large population-based survey to measure the proportion of depressed Canadian Armed Forces (CAF) personnel who self-reported using mental health services in the past 12 months. Second, I conducted a systematic review to compare the major depression treatment gap uncovered in the first study to the treatment gaps reported in other military organizations. Third, I used data extracted from electronic medical records to measure the rate of new major depression diagnoses in CAF personnel. Results were highly consistent with the treatment gap estimates obtained from the first study, and this helped confirm the quality of the novel electronic medical record data. Fourth, I used data extracted from CAF electronic medical records to measure the temporal association between incident major depression and spinal pain. Because electronic medical records can only identify depression in care-seeking patients, I used quantitative bias analysis methods and the treatment gap estimates obtained from the first study to mitigate the risk of misclassification bias. The results of these four studies suggest that the major depression treatment gap is smaller in the Canadian military than it is elsewhere, but that it could be further reduced with additional mental health literacy interventions. They also suggest that certain sub-groups of CAF personnel may benefit from enhanced prevention or screening efforts, including spinal pain patients and individuals newly posted to administrative cells for severely sick or injured personnel. Finally, these studies highlight the importance of using rigorous epidemiological methods in military major depression research.
Keywords: Depression; Epidemiology; Mental Health; Military